Behavioral studies of surge protection components - Teik Hua Kuan; Kuew Wai Chew; Kein Huat Chua (Institute of Advanced Engineering and Science, 2021)
In our daily life, almost all the items we used, being a computer, television, lift or vehicle we drive consist of some kind of electrical or electronics component inside. The operation of these devices could be severely affected by lightning activity or electrical switching events, as there are more than 2000 thunderstorms in progress at any time resulting in 100 lightning flashes to ground per second. In practice, any device using electricity will subject to surge damages induced from the lightning or switching of heavy load. Surge protection device (SPD) is added at the power distribution panel and critical process loop to prevent damage subsequently cause plant shutdown. There are many questions raised on the SPD. How can this small device protect the equipment from large energy release by the lightning? What is inside the device? How does it work? This paper provides comprehensive detail in revealing the science and engineering behind the SPD, its individual component characteristic and how does it work. The technical information presented is limited to surge protection on equipment; surge protection for building structure will not be discussed here.